2016
DOI: 10.4049/jimmunol.1502342
|View full text |Cite
|
Sign up to set email alerts
|

Rac GTPase Activating Protein ARHGAP25 Regulates Leukocyte Transendothelial Migration in Mice

Abstract: ARHGAP25 is a Rac-specific GTPase-activating protein that is expressed primarily in hematopoietic cells. The involvement of ARHGAP25 in regulating the recruitment of leukocytes to inflammatory sites was investigated in genetically modified mice. Using intravital microscopy, we show that Arhgap25 deficiency affects all steps of leukocyte recruitment with a predominant enhancement of transendothelial migration of neutrophilic granulocytes. Increased transmigration of Arhgap25-deficient leukocytes is demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Increased trafficking of RhoA/B deficient PMN was also observed in vivo following sterile inflammation induced by thioglycolate [38]. ARHGAP25 is a Rac-specific GAP expressed by PMN, and similar to what was found for RhoA, it has been reported that loss of ARHGAP25 expression leads to a pro-inflammatory phenotype with increased PMN Rac activation and elevated transmigration into inflamed tissues [39]. Bcr and Abr are GAPs that contain binding sites for a number of signal transduction proteins including tyrosine kinases, serine/threonine kinases and scaffolding proteins.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Increased trafficking of RhoA/B deficient PMN was also observed in vivo following sterile inflammation induced by thioglycolate [38]. ARHGAP25 is a Rac-specific GAP expressed by PMN, and similar to what was found for RhoA, it has been reported that loss of ARHGAP25 expression leads to a pro-inflammatory phenotype with increased PMN Rac activation and elevated transmigration into inflamed tissues [39]. Bcr and Abr are GAPs that contain binding sites for a number of signal transduction proteins including tyrosine kinases, serine/threonine kinases and scaffolding proteins.…”
Section: Introductionmentioning
confidence: 87%
“…GTPase-activating proteins (GAPS), have been shown to suppress PMN functions such as phagocytosis, ROS production, and degranulation by inhibiting the activation of Rac and F-actin polymerization [39, 40, 56, 57, 61]. Vav-1 and TIPE-2 also inhibits Rac activation and therefore, suppress ROS production [59, 60].…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Depletion of FilGAP in normal epithelial MDCK (Madin Darby canine kidney) cells also increased the migration speed and cell scattering induced by Hepatocyte growth factor (Nakahara et al, 2015). ARHGAP25 is expressed primarily in hematopoietic cells and regulates leukocyte migration (Csépányi-Kömi et al, 2016). ARHGAP22 suppresses EGF-induced lamellae formation and cell spreading on fibronectin (Mori et al, 2014) and regulates cell migration downstream of Akt signaling in fibroblasts (Rowland et al, 2011).…”
Section: Regulation Of Cell Morphology and Migration Bymentioning
confidence: 99%